Effect of pulse-reverse plating on copper: Thermal mechanical properties and microstructure relationship. (May 2019) - Huang, Bau-Chin; Yang, Cheng-Hsien; Lee, Cheng-Yu; Hu, Yu-Lung; Hsu, Chi-Chang; Ho, Cheng-En
Abstract: Copper electrodeposition in a high aspect-ratio (AR) through hole (TH) structure is a critical reliability issue in automotive printed circuit boards (PCBs). We investigated the plating through hole (PTH) via direct current (DC) and pulse-reverse (PR) electroplating Cu, where the forward plating current density ( j f ) of 2 A/dm 2 and reverse current density ( j r ) of 6 A/dm 2 with various PR frequency of pulse plating time ( t on )/reverse stripping time ( t rev ) = 20/1, 60/3, and 100/5 [ms/ms] were examined. The Cu deposition behavior (throwing power) and its crystallographic characteristics, including grain size, crystallographic orientation, and grain boundary, were characterized by means of X-ray computed tomography (X-ray CT), field-emission scanning electron microscopy (FE-SEM), and electron backscatter diffraction (EBSD). Moreover, the thermal reliability of the automotive PCBs was evaluated via the thermal cycling test (TCT) in the temperature range from −40 °C to 125 °C. After TCT for 500 cycles, numerous cracks formed in the Cu platings with t on / t rev  = 100/5 [ms/ms], which inevitably degraded the thermomechanical and electrical characteristics of the PTH structure. The dependence of the Cu microstructure on the PR frequency, and the underlying mechanism of the crack formation in Cu will be discussed. Highlights: X-ray CT provides a non-destructive analysis of the Cu electrodeposition in PTH. The uniformity of Cu electrodeposition can be greatly improved via PR plating. Cu crystallographic microstructure strongly depends on the PR frequency. Twin formation can be enhanced by increasing PR frequency. TCT reliability can be greatly improved by increasing twin boundaries in Cu.